An innovative technique for surgical positioning in head and neck surgery - Mohd Firdaus CA,; Hardip Singh Gendeh,; Nik Ritza Kosai Nik Mahmood,; Farrah Hani Imran,; Mohd Ramzisham Abdul Rahman, (Fakulti Perubatan, UKM, 2016)
Patient positioning is a vital in ensuring patient comfort, dignity and good access to the operative site. Accurate positioning helps in minimising the risk of injury to the patient. An in-house airbag made from recyclable medical supplies can be used to replace the conventional sandbag for head and neck surgeries. It involves the use of an empty irrigation bottle, a valve and suction tubing. Its shape and volume is readily adjustable by altering the volume of inflated air. Moreover, compressible air moulds the bag to the curvature of the patient’s external surface reducing the risk of pressure sores in prolonged surgery. Ultimately this serves as an innovative technique which is financially savvy with the use of recyclable items.